GROWTH AND PRODUCTION OF SORGHUM (SORGHUM BICOLOR L.) TO BOKASHI APPLICATION IN DRYLAND OF SOUTH SUMATRA - Kawaty, Ruarita Ramadhalina; Mukminah, Faridatul; Utami, Arinda (ITScience (Information Technology and Science), 2023)
The aims of this study were to find out how the growth and yield of sorghum (Sorghum bicolor L.) responds to the application of bokashi fertilizer and got the best dose of bokashi fertilizer for growth and yield of sorghum. This study was designed using a Randomized Block Design (RBD) experimental method. Giving of bokashi fertilizer with various dosages in sorghum plants can give a good response to the growth and production of sorghum plants. Giving of bokashi fertilizer with a dosage of 15 tons/ha or equivalent to 6.48 kg/plot (P3) resulted better plant growth than other treatments, with an average plant height of 204.94 cm at the age of 56 days after planting (DAP), the number of tillers flat average 5.50 tillers at the age of 28 DAP, fastest flowering age was 55.75 DAP, average wet biomass 1710.25 g/plant, fresh weight cobs in average of 129.06 g/plant, average yield was 1892,50 g/plot, average of weight of 1000 seeds was 12.63 g. Giving of bokashi fertilizer with a dosage of 17.5 tons/ha or equivalent to 7.56 kg/plot (P4) resulted the number of leaves in average of 17.69 at the age of 56 DAP and panicle length average of 40.06 cm. Giving of bokashi fertilizer with a dosage of 10 tons/ha or equivalent to 4.32 kg/plot (P1) resulted the number of panicle branches in average of 46.75 branches.